Dutilh & Wachsmuth (Philadelphia, Pa.) records - Dutilh & Wachsmuth (Philadelphia, Pa.)
Business correspondence, accounts, documents relating to trade with other shipping houses in Europe, America, and the West Indies; names of French refugee passengers (1792-1800) from the West Indies; the shipment of firearms and other goods to Ft. Pitt, Pa. (1785), and the slave trade.
Collection material in French, with Dutch and English.
Keywords: Firearms industry and trade; Fortification -- Pennsylvania; Merchants -- Pennsylvania -- Philadelphia; Military bases -- Pennsylvania; Refugees -- West Indies; Slave trade; America -- Commerce -- United States; Europe -- Commerce -- United States; Fort Pitt (Pa.); Philadelphia (Pa.) -- Commerce; United States -- Commerce -- America; United States -- Commerce -- Europe; United States -- Commerce -- West Indies; West Indies -- Commerce -- United States